Empowering community cadres through digital developmental screening using the e-KPSP application at Posyandu Panca Marga 8 - Rodliya, Adzka Fahma; Tahir, Erni Susanty; Utami, Anisa Putri; Kaeksi, Ika Restu; Mandariska, Resa Paksi (Faculty of Medicine, Public Health, and Nursing, Universitas Gadjah Mada, 2026)
Introduction: Early detection of developmental problems in early childhood is essential. However, community health services often prioritize growth monitoring over developmental surveillance. Community health cadres, who are central to Posyandu activities, require strengthened capacity and confidence to implement systematic screening. This study aimed to improve community empowerment through the implementation of digital developmental screening using the e-KPSP application at Posyandu Panca Marga 8, Kartasura District, Indonesia, with a particular focus on analyzing cadre acceptability.Methods: The intervention was conducted over six months from February to August 2025, involving 15 trained cadres and 55 children aged 3–59 months. Program stages included socialization with mothers and cadres, cadre training, digital screening implementation, and structured monitoring and reporting. Acceptability was measured using a validated questionnaire before and after the intervention.Results: Results revealed statistically significant improvements across all acceptability dimensions. Perceived Benefits increased from a mean of 38.07 to 53.00 (p < 0.001), Satisfaction from 13.47 to 18.00 (p < 0.001), Care Personnel Concern decreased from 10.53 to 4.93 (p = 0.005), Privacy and Discomfort decreased from 7.73 to 6.07 (p < 0.001), and Kit as Substitution decreased from 9.60 to 4.80 (p = 0.006). The overall acceptability score showed a significant improvement (Wilcoxon Signed-Rank Test, p = 0.005).Conclusion: These findings demonstrate that digital developmental screening using the e-KPSP application is well-accepted by cadres and effectively supports the integration of developmental surveillance into routine community health services.